1976
DOI: 10.1136/jcp.29.10.955-a
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control for Coulter Counter Models

Abstract: In this laboratory, we have been using a method of quality control for our Coulter Model S which is not related to commercial whole blood standard preparations. In the national quality control trials, it has been found consistently that participants using Coulter S produce a lower mean value for haemoglobin than with other systems and, although the difference is in the order of 0-2-0-3 g/dl, 0.5 g/dl is just within 2 SD. Although there is no definite information, it seems likely that this discrepancy is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1979
1979

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…equipment. It appeared that some laboratories were Prangnell and Johnson (1976) showed that the stated using commercial reference controls as standards and value for haemoglobin for a commercial reference not checking against a cyanmethaemoglobin control differed by 0 5 g/dl from the reference standards approved by the ISCH. Platelet count results varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…equipment. It appeared that some laboratories were Prangnell and Johnson (1976) showed that the stated using commercial reference controls as standards and value for haemoglobin for a commercial reference not checking against a cyanmethaemoglobin control differed by 0 5 g/dl from the reference standards approved by the ISCH. Platelet count results varied greatly.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent letter to the Editor, Prangnell and Johnson (1976)1 pointed out that, using a Coulter Counter S with calibration of the haemoglobin levels against three cyanmethaemoglobin standards, the results averaged 0 5 g/dl higher than in laboratories using Coulter 4C to calibrate their machines. In the same way, Lewis (1976), in a comment on this letter, says that in the national quality control trials it has been found that participants using Coulter S produce a lower mean value for haemoglobin than when using other systems, although the difference is in the order of 0-2-0-3 g/dl; 0 5 g/dl is just within 2SD.…”
Section: Letters To the Editormentioning
confidence: 99%